State Policy of Serbia – National Communities, Citizenship and Diaspora - Radosavljević, Duško (Bałkany Zachodnie w systemie bezpieczeństwa euroatlantyckiego, Bałkany XX/XXI, t. 7, 2015)
The author will try to present some of the basic legal acts which define the position of national communities, the status of the Romanies in general, since the Romanies as a community have been in the most unfavourable position.